FACTORS AFFECTING FINANCIAL DISTRESS IN MANUFACTURING COMPANIES LISTED ON THE IDX - Salim, Agusti Fransisca; Yanti, Yanti (International Journal of Application on Economics and Business, 2023)
In this study, the causes of financial distress in manufacturing firms listed on the Indonesia Stock Exchange from 2018 to 2020 were investigated. These factors include profitability (as measured by return on assets [ROA]), liquidity (as measured by current ratio [CR]), sales growth (as measured by sales growth rate), leverage (as measured by debt to assets [DAR]), firm size (as measured by the logarithm of total assets), and operating capacity (as measured by total assets turnover [TATO]). Based on the purposive sampling strategy, 99 data from 33 organizations were chosen as research samples. The EViews 12 was used to test the data processing in this investigation. This study's analysis employed a multiple regression analysis approach. The findings of this study indicate that financial distress is significantly and negatively influenced by firm size. Profitability, liquidity, and operating capacity, on the other hand, have a positive and significant impact on financial distress. Leverage and sales growth have no impact on financial distress.